Bond strength between steel reinforcement and RCA concrete during and after exposure to elevated temperatures. (22nd August 2022) - Yusuf, M.; Sarhat, S.; Hajiloo, H.; Green, M.F.
Highlight: RCA concretes showed adequate bond strength during and after exposure to high temperatures. Residual bond strengths of all concretes are lower than their steady-state bond strengths. Higher bond deformations (slips or strokes) were recorded in RCA concretes than NAC. Bond strength in transient scenario depends on the degree of exposure and preloading level. Bond deterioration is related to deterioration in the mechanical properties of concrete. Abstract: Studies exist on the performance of recycled concrete aggregate (RCA) concrete under different loading conditions at both material and structural levels. However, less attention has been directed to studying the bond strength between steel reinforcement and RCA concrete, especially when exposed to elevated temperatures. This paper presents an extensive experimental study on the bond response of RCA concrete during and after exposure to elevated temperatures. Three concrete mixes were studied, one natural aggregate concrete (NAC) and two RCA concretes. Two different mixing methods were used to proportion the RCA concretes, one by the conventional volume method and one by the equivalent mortar method. In total, 72 pullout specimens were cast and heated under different scenarios: 20 °C (ambient temperature), at four different elevated temperatures of 200, 300, 400, and 550 °C without preloading (steady-state), during heating while being preloaded with 20%, 35% and 75% of the ambient strength (transient), and after heating to 550 °C and then cooling down to ambient (residual). Also, concrete cylinders were cast and tested to measure the compressive and tensile strength at different heating scenarios. The results revealed that the RCA specimens exhibited adequate bond performance and retained comparable bond strengths to the NAC ones during and after exposure to elevated temperatures. However, higher bond deformations (or slip) were recorded in RCA concretes than in NAC. The results showed that the bond strength response in the transient scenario depends mainly on the degree of exposure to elevated temperatures and on the preloading level. The results also showed that the deterioration in the bond strength due to exposure to elevated temperatures is related to the deterioration in the mechanical properties, especially the splitting tensile strength of concrete.